Meningkatkan Kemampuan Membaca Permulaan Melalui Kegiatan Mendongeng dengan Variasi Media di KB PAUD PKK Wonojoyo Kediri - Alfin Zainun Faiz (Universitas Trunojoyo Madura, 2017)
This study aims to improve the ability to read the beginning through the activities of storytelling with media variations and know the process of improving the ability to read the beginning through the storytelling activities with media variations. The research method used is action research with Kemmis and Taggart model. Research subjects were 16 KB children. This study was conducted in two cycles consisting of eight meetings in a cycle so that there were sixteen meetings. Technique of collecting data is done through observation, interview, and documentation. Data analysis technique used in this research is qualitative and quantitative data analysis. Qualitative data analysis used is data reduction, data display, and verification. Quantitative data analysis is used to find out the percentage of reading ability improvement after the beginning of the implementation of the action using the graph. The result of the research shows that the improvement of the understanding of children's geometry can be seen from the average prasiklus value of 58, the average of cycle I average 77, and cycle II with an average of 90. So it can be concluded that the activities of storytelling with media variations can improve the ability to read the beginning